Toward mucoadhesive hydrogel formulations for the management of xerostomia: The physicochemical, Biological, and Pharmacological Considerations. Issue 11 (25th March 2013) - Tsibouklis, John; Middleton, Andrew M.; Patel, Nisha; Pratten, Jonathan
<x xml:space="preserve">Abstract</x> Although hydrogel formulations that may be applied to many mucosal surfaces are now readily accessible, little research effort has been concentrated on the development of systems that may be usefully employed for the prolonged hydration of the oral cavity. To this end, and set within the context of oral care in general, this review considers the requirements for the design of hydrogel formulations with an affinity for buccal cells and details methods for evaluating the performance of these formulations as treatments for the management of xerostomia. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3327–3338, 2013.